2021
DOI: 10.1002/adma.202102660
|View full text |Cite
|
Sign up to set email alerts
|

Tethering Cells via Enzymatic Oxidative Crosslinking Enables Mechanotransduction in Non‐Cell‐Adhesive Materials

Abstract: proliferation, apoptosis, metabolism, and differentiation. [1,2] However, the variety of strategies to control cell-biomaterial interactions able to transmit mechanical cues from the microenvironment to the cells within engineered tissue constructs has remained limited and near-exclusively relied on cell adhesion. Biomaterials are typically endowed with bioligands that bind to cell adhesion molecules (CAMs; e.g., integrins, cadherins, and selectins). The integrinbinding tripeptide arginine-glycine-aspartic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 99 publications
4
11
0
Order By: Relevance
“…Photo‐initiated postcuring of SCMs could be controlled via the ruthenium complex concentration, thereby endowing SCMs with the capacity to predictably acquire a well‐defined physiological stiffness following exposure to a noninvasive visible light‐based trigger (Figure 5b ). In line with literature, [ 8f ] hydrogel stiffness linearly ( R 2 = 0.96) correlated with EthD‐1 staining intensity (Figure 5c ). This allowed for noninvasive visualization and quantification of SCM stiffness within composite microtissues before and after visible‐light‐induced postcuring at high spatial resolution.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Photo‐initiated postcuring of SCMs could be controlled via the ruthenium complex concentration, thereby endowing SCMs with the capacity to predictably acquire a well‐defined physiological stiffness following exposure to a noninvasive visible light‐based trigger (Figure 5b ). In line with literature, [ 8f ] hydrogel stiffness linearly ( R 2 = 0.96) correlated with EthD‐1 staining intensity (Figure 5c ). This allowed for noninvasive visualization and quantification of SCM stiffness within composite microtissues before and after visible‐light‐induced postcuring at high spatial resolution.…”
Section: Resultssupporting
confidence: 90%
“…Individual MSCs in hydrogel could differentiate towards the osteogenic lineage, which corresponded to previous studies focusing on stiffness‐controlled differentiation of MSCs in hydrogels (Figure 4b ). [ 8 , 34 ] Cell‐only spheroids embedded in hydrogel were characterized by negligible levels of osteogenesis, which corroborated a previous study that reported on the encapsulation of MSC spheroids in soft versus stiff hydrogels. [ 21 ] Interestingly, engineering composite microtissues where stiff SCMs are located in between MSCs not only fully rescued the osteogenic differentiation, but demonstrated a calcification level that significantly surpassed the conventional cells‐in‐hydrogel composition (Figure 4c ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, Jeroen Leijten and co-workers have demonstrated the discrete inducible oncell crosslinking (DOCKING) of no-cell-adhesive tyraminefunctionalized dextran biomaterials onto stem cells via the oxidative crosslinking of phenolic moieties, enabling mechanotransduction via the a-actinin axis according to proteomic analysis, which indicates the promising role of DOCKING as a unique tool for optimizing tissue engineering applications. 136 Last but not the least, the possible undesired long-term side effects (e.g., fibrosis or calcification) of the polyphenolic systems should be considered thoroughly and carefully, particularly as implantation materials. Collectively, indebted by the advancements of chemistry and biology interdisciplinary, more kinds of bioactive and innovative polyphenolic materials are expected to be developed and explored, as well as translated into various clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Information is collected from published works. 20,21,[135][136][137][138][139][140][141][142] crosslinked with EGCG and TA are mechanically stiffer compared to the rest. Moreover, the laser-induced graphitization of PDA could strengthen its mechanical properties and maintain multifunctionality.…”
Section: Stiffnessmentioning
confidence: 99%